Broadband fixed wireless access as a key component of the future integrated communications environment. - Webb, W. (IEEE Communications magazine)
It is an exciting time for broadband fixed wireless with key developments in frequency bands from 1 to 60 GHz and a range of new technologies being developed. While working on these new technologies, it is easy to forget that fixed wireless access will form part of an integrated communications environment of the future where users will have one communications device working in the home, at the office, and outdoors. This article predicts the communications environment of the next 20 years and looks at the role of fixed access within that environment. This involves assessing how fixed access systems will interface and integrate with in-home wireless networks, how their architecture will enable multiservice operators to utilize the same core network across a range of different access technologies, and how they will act as a channel to carry mobile traffic originating within the building. Based on the requirements this vision and architecture implies, this article critically assesses the different fixed wireless technologies available to date and compares their capabilities to provide future-proof broadband fixed wireless platforms